Defect‐Enhanced CO2 Reduction Catalytic Performance in O‐Terminated MXenes. Issue 21 (9th September 2020) - Chen, Hetian; Handoko, Albertus D.; Wang, Tianshuai; Qu, Jiale; Xiao, Jiewen; Liu, Xiaopeng; Legut, Dominik; Wei Seh, Zhi; Zhang, Qianfan
Abstract: Electrochemical carbon dioxide reduction reaction (CO2 RR) represents a promising way to generate fuels and chemical feedstock sustainably. Recently, studies have shown that two‐dimensional metal carbides and nitrides (MXenes) can be promising CO2 RR electrocatalysts due to the alternating −C and −H coordination with intermediates that decouples scaling relations seen on transition metal catalysts. However, further by tuning the electronic and surface structure of MXenes it should still be possible to reach higher turnover number and selectivities. To this end, defect engineering of MXenes for electrochemical CO2 RR has not been investigated to date. In this work, first‐principles modelling simulations are employed to systematically investigate CO2 RR on M2 XO2 ‐type MXenes with transition metal and carbon/nitrogen vacancies. We found that the −C‐coordinated intermediates take the form of fragments (e. g., *COOH, *CHO) whereas the −H‐coordinated intermediates form a complete molecule (e. g., *HCOOH, *H2 CO). Interestingly, the fragment‐type intermediates become more strongly bound when transition‐metal vacancies are present on most MXenes, while the molecule‐type intermediates are largely unaffected, allowing the CO2 RR overpotential to be tuned. The most promising defective MXene is Hf2 NO2 containing Hf vacancies, with a low overpotential of 0.45 V. More importantly, through electronic structure analysis it could be observed that the Fermi level of the MXene changes significantly in the presence of vacancies, indicating that the Fermi level shift can be used as an ideal descriptor to rapidly predict the catalytic performance of defective MXenes. Such an evaluation strategy is applicable to other catalysts beyond MXenes, which could enhance high throughput screening efforts for accelerated catalyst discovery. Abstract : Enhancing catalytic performance through vacancies : Vacancies influence the binding energy of intermediates and further affect the limiting potential of the electrochemical carbon dioxide reduction reaction. The catalytic performance of MXenes can be enhanced by introducing a suitable defect type. Furthermore, the shift of Fermi level can be a simple yet promising descriptor to predict the effect exerted by vacancies.